Nasrin’s French Lover: Women’s Lives in Bangladesh - Adhikari, Tara Prasad (Nepal Journal of Multidisciplinary Research, 2025)
Background: This paper analyzes Taslima Nasrin’s French Lover (2001) as a critique of patriarchal structures in Bangladeshi society. The study focuses on the protagonist, Nilanjana, and her struggle for identity and autonomy. The novel highlights how a patriarchal culture, compounded by its own rigid religious beliefs, targets women’s and defines their lives in relation to men— often at the cost of their own freedom and identity. Methodology: This study draws on Simone de Beauvoir’s concept of woman as “Other,” Abeda Sultana’s analysis of patriarchal subordination. It will also use Taslima Nasrin’s own critique of gender norms to examine Nilanjana’s journey in relation to other Bangladeshi women. A close textual analysis will be run to explore themes of marriage, societal expectations, and resistance. The novel will set the broader context of gender dynamics in South Asia at the central stage to illuminate the lives of South Asian Women. Results: The narrative reveals a visible impact of patriarchal expectations on the women characters, as their identity is shaped by their roles as daughter, wife, and potential mother, thereby restricting their personal desires. Nilanjan’s marriage to Kishanlal, driven by societal pressure rather than love, reflects the systemic denial of female agency. Her eventual pursuit of independence in France signifies a rejection of those societal constraints. The novel critiques the societal scrutiny of women’s appearance and behavior as well because these gazing behaviors would force women to be a conformist at the expense of their own freedom. Conclusion: French Lover foregrounds the challenges Bangladeshi women face in asserting their identities within a patriarchal framework. Nilanjana’s journey toward self-discovery offers a vision of resistance and empowerment. This study brings in the glaring examples from the text to highlight how patriarchy has limited the lives of Bangladeshi women and what needs to be done to fight back. The study calls for a redefinition of female identity that embraces autonomy and individuality. Novelty: This study highlights Nasrin’s contribution to feminist discourse by illustrating how French Lover critiques the intersection of gender, culture, and identity with reference to Bangladesh. Bangladeshi women’s stories are usually unheard because of the strict religious code of conducts therefore this study tries to get into the lives of Bangladeshi women through Nashree’s narratives, highlighting the novel’s relevance to contemporary discourses on gender equality in traditional societies.